Correlation of Proliferative Marker in B & T Non-Hodgkin’s Lymphoma (NHL) by Immunohistochemical Expression with Ki-67, CD20, and CD3 Tumor Markers: Clinicopathological Study - Asaad Hashim Jaber; Ali Fadhil Hashim; Talib Jwad Kadhim; Maha Sabah Majeed (Karbala Journal of Medicine, 2025)
Background: Tumor proliferation is a fundamental process in cancer progression. Ki-67, a nuclear antigen, is widely recognized as a reliable marker for evaluating cell proliferation through immunohistochemical analysis. Its expression is restricted to the active phases of the cell cycle (G1, S, G2, and M), making it a valuable tool in assessing tumor proliferative activity. In the context of non-Hodgkin lymphomas (NHL), Ki-67 serves as a potential indicator for tumor aggressiveness and clinical behavior. This study aims to evaluate the association between Ki-67, CD20, and CD3 expressions and the clinicopathological features of NHL, including its role in disease progression, response to treatment, and its correlation with variables such as age, gender, type, and tumor location, in order to enhance diagnostic and prognostic accuracy. Methods: A retrospective analysis was conducted on forty formalin-fixed paraffin-embedded excisional biopsies of NHL cases collected between June 2021 and February 2022 from a specialized surgical center in Baghdad Medical City. All samples were re-evaluated histologically and stained immunohistochemically for Ki-67, CD20, and CD3 markers. Statistical analysis was performed, with significance set at P<0.05. Results: A statistically significant association was found between the Ki-67 labeling index and both lymphoma grade and immunophenotypic type. Based on CD3 and CD20, 30 (75%) had B-cell NHL and 10 (25%) had T-cell NHL. Conclusions: The study highlights the strong correlation between Ki-67 expression and lymphoma grade. Notably, high-grade lymphomas, especially those with extranodal spread, were predominantly seen in pediatric patients. Keywords: Non-Hodgkin's lymphoma, Ki-67, CD3, CD20, Proliferative index, Lymphoma grade